Sino-Indian Climate Cooperation under Global Development Initiative: History, Challenges and Opportunities - Qin, Shuyu (Transactions on Social Science, Education and Humanities Research, 2024)
In 2021, President Xi Jinping put forward the Global Development Initiative, and climate change is the key cooperation area of the initiative. Both China and India are developing countries and share many common interests in climate control, which has laid a solid foundation for climate cooperation between the two countries. Sino-Indian climate cooperation began in the 1990s and has gone through many stages, such as exploration, preliminary cooperation, and collaborative leadership. The two countries have conducted extensive cooperation in tackling climate change, reducing greenhouse gas emissions, and developing renewable energy, and have achieved fruitful results. However, China and India also face many challenges in climate cooperation, such as territorial boundaries and differences in economic development. Nevertheless, both sides are aware of their complementary advantages and common national interests, which has created favorable conditions for further deepening cooperation. On the whole, China and India have more opportunities than challenges in the field of climate cooperation; At the same time, the Global Development Initiative will inject new impetus into the cooperation between China and India in the field of climate change. Under the guidance of this initiative, China and India will further strengthen cooperation, jointly meet the challenges brought by global climate change, and promote the construction of a more sustainable and prosperous world.